Prototype development of a computerized system for interpretation of heart sounds using wavelet - Brites, Ivo Sérgio Guimarães; Oki, N. (Springer Nature, 2014)
Monitoring of the changes of heart sounds provide information about the heart condition. Compared to other methods of monitoring heart condition, heart sound monitoring is cheaper and safer. This paper aims to design a system for automatic analysis of heart sounds using the Discrete Wavelet Transform for extracted its features. Experiments with database compose of heart sound healthy and with pathologies show that the system proposed was able to discern the normal or abnormal sound with the error of 90%. © Springer International Publishing Switzerland 2014.
Keywords: Classification of signals; Database; Discrete wavelet; Heart auscultation; Heart sounds